India’s Food-Security Governance Under the Modi Administrations - IVICA PETRIKOVA (The Journal of Indian and Asian Studies, 2022)
This article reviews the state and governance of India’s food security, with a specific focus on developments under the Modi/BJP administrations since 2014. Whilst the discourse of Modi/BJP administrations suggests a significant departure from previous administrations’ governance approaches, I find that the governance of both macro-level and micro-level food security in India has remained broadly unchanged over the past few decades. Macro-level aspects of food security, food availability and food stability, continue to be governed through the framework of the Public Distribution System (PDS) and Minimum Support Prices paid out to farmers for the cultivation of rice and wheat. Micro-level aspects of food security, food access and food utilization, remain managed through a network of social programs, primarily the PDS, the Integrated Child Development Services, and the Mid-Day Meals Scheme. One key difference has been a greater success of the Modi administrations in tying the programs’ achievements, even if modest, directly to Modi and the BJP, giving the BJP an electoral boost. The focus on short-term political gains has, however, undermined India’s governance effectiveness and with it its ability to implement policies capable of addressing India’s longer-term structural food-security challenges.